2015
DOI: 10.1073/pnas.1416776112
|View full text |Cite
|
Sign up to set email alerts
|

Microbial denitrification dominates nitrate losses from forest ecosystems

Abstract: Denitrification removes fixed nitrogen (N) from the biosphere, thereby restricting the availability of this key limiting nutrient for terrestrial plant productivity. This microbially driven process has been exceedingly difficult to measure, however, given the large background of nitrogen gas (N 2 ) in the atmosphere and vexing scaling issues associated with heterogeneous soil systems. Here, we use natural abundance of N and oxygen isotopes in nitrate (NO 3 − ) to examine dentrification rates across six forest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
125
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 192 publications
(147 citation statements)
references
References 37 publications
18
125
0
2
Order By: Relevance
“…Heterotrophic NO 3 − immobilization also fractionates against O and N isotopes in NO 3 − ; though at a much higher slope, typically between 1.0 and 2.0 (Granger et al, 2010). Our observed 0.55 slope for field sites (R 2 = 0.25, P = 0.00026) is therefore consistent with the imprint of terrestrial denitrifiers on soil NO 3 − consumption (Figure 3), as seen in previous work in tropical and temperate forest soils (Houlton et al, 2006;Fang et al, 2015). We cannot specifically address why the slopes differ across studies, but past work on marine bacteria cultures indicates that chemolithotrophs fractionate a slope closer to 0.5, whereas heterotrophic denitrifiers appear to fractionate O and N isotopes at a higher slope (Frey et al, 2014).…”
Section: Terrestrial Denitrification In Genes To Ecosystems Efe Lennosupporting
confidence: 89%
See 2 more Smart Citations
“…Heterotrophic NO 3 − immobilization also fractionates against O and N isotopes in NO 3 − ; though at a much higher slope, typically between 1.0 and 2.0 (Granger et al, 2010). Our observed 0.55 slope for field sites (R 2 = 0.25, P = 0.00026) is therefore consistent with the imprint of terrestrial denitrifiers on soil NO 3 − consumption (Figure 3), as seen in previous work in tropical and temperate forest soils (Houlton et al, 2006;Fang et al, 2015). We cannot specifically address why the slopes differ across studies, but past work on marine bacteria cultures indicates that chemolithotrophs fractionate a slope closer to 0.5, whereas heterotrophic denitrifiers appear to fractionate O and N isotopes at a higher slope (Frey et al, 2014).…”
Section: Terrestrial Denitrification In Genes To Ecosystems Efe Lennosupporting
confidence: 89%
“…Moreover, the spatial patterns observed across sites are similarly observed in our short-term incubation experiments (that is, 7 days), thus pointing to the importance of microbial denitrifiers in driving soil NO 3 − availability patterns in both space (Lehmann et al, 2003;Granger et al, 2008) and observations for other terrestrial ecosystems (Houlton et al, 2006;Fang et al, 2015), similar to the spatial relationships observed for all samples across sites (that is,~0.6) ( Figure 6). Not only did we observe a positive relationship between nirS and δ 15 N-NO 3 − mirroring the cross-system results; but there was a significant positive correlation between nirS/16S rRNA and δ 15 N-NO 3 − in our soil incubation experiments as well (R 2 = 0.70, P = 0.001) (Figure 7).…”
Section: Terrestrial Denitrification In Genes To Ecosystems Efe Lennosupporting
confidence: 79%
See 1 more Smart Citation
“…Yet, the capacity for denitrification can rapidly increase once waterlogged conditions develop in riparian zones (Harms et al, 2009). Indeed, along larger stream orders under these climatic conditions, soil development, including accretion of fine sediment texture and organic matter increase the water residence time and in turn denitrification capacity (Fang et al, 2015;Tiwari et al, 2017;Malone et al, 2018). We recognize that many ecological and climatological dynamics interrupt these broad patterns, which we present only as general predictions to be tested across biomes.…”
Section: Riparian Corridors Function As Kidneys Of River Systemsmentioning
confidence: 80%
“…As with mineralization, the potential for nitrogen retention and removal can vary dramatically between climatic regions, especially because denitrification, one of the main processes responsible for nitrogen removal, is highly dependent on soil moisture conditions and nitrate supply. In tropical and temperate regions, denitrification can account for up to half of the total ecosystem nitrogen losses (Hefting et al, 2004;Houlton et al, 2006;Fang et al, 2015). We hypothesize that denitrification represents a significant part of the N cycling in tropical riparian zones, whatever the stream order (McClain et al, 1994;Décamps et al, 2004;Houlton et al, 2006).…”
Section: Riparian Corridors Function As Kidneys Of River Systemsmentioning
confidence: 89%